2021
DOI: 10.3390/ijms22083928
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Leukocyte Biomarkers Related to Drug Recovery of CFTR: Clinical Applications in Cystic Fibrosis

Abstract: The aim of this study was the identification of specific proteomic profiles, related to a restored cystic fibrosis transmembrane conductance regulator (CFTR) activity in cystic fibrosis (CF) leukocytes before and after ex vivo treatment with the potentiator VX770. We used leukocytes, isolated from CF patients carrying residual function mutations and eligible for Ivacaftor therapy, and performed CFTR activity together with proteomic analyses through micro-LC–MS. Bioinformatic analyses of the results obtained re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
4
11
0
Order By: Relevance
“…A limited description of specific affected proteins involved in phagocytosis was provided, however proteins such as LEMD2 (transmembrane adapter for ESCRT) and ACTG1 were altered by ivacaftor, suggesting a potential impact on degradative and actin-related processes. In a separate proteomics study, several proteins involved in the regulation of actin cytoskeleton and leukocyte trans-endothelial migration were strongly downregulated in CF monocytes carrying residual function CFTR variants after treatment with ivacaftor [ 177 ]. In a fourth study, people with CF treated with lumacaftor/ivacaftor had a lower expression of CXCR2 (receptor for IL-8) on CD14+ CD16- monocytes compared to healthy controls.…”
Section: Cftr Modulators/other Therapeutics and Cf Phagocytosismentioning
confidence: 99%
“…A limited description of specific affected proteins involved in phagocytosis was provided, however proteins such as LEMD2 (transmembrane adapter for ESCRT) and ACTG1 were altered by ivacaftor, suggesting a potential impact on degradative and actin-related processes. In a separate proteomics study, several proteins involved in the regulation of actin cytoskeleton and leukocyte trans-endothelial migration were strongly downregulated in CF monocytes carrying residual function CFTR variants after treatment with ivacaftor [ 177 ]. In a fourth study, people with CF treated with lumacaftor/ivacaftor had a lower expression of CXCR2 (receptor for IL-8) on CD14+ CD16- monocytes compared to healthy controls.…”
Section: Cftr Modulators/other Therapeutics and Cf Phagocytosismentioning
confidence: 99%
“…The label-free quantitation was performed through MS signal intensity with total peptide normalization. The abundances of the proteins, exported by PD 2.4 software, were used for PCA and hierarchical cluster analysis using MetaboAnalyst 5.0 (www.metaboanalyst.org; Date accessed: 12 May 2021) [60]. Proteins with an adjusted p-value < 0.01 and a fold change ≥2 were considered differentially expressed.…”
Section: Nano-uplc-ms/ms and Comparative Proteomic Analysismentioning
confidence: 99%
“…Indeed, studies on CFTR deficient pigs have shown altered responses of monocytes to pathogens tested on Pseudomonas aeruginosa infections [ 40 ], are in agreement with other modeling systems demonstrating a difference between the CFTR deficient environment and the healthy, non-CF environment [ 41 , 42 , 43 , 44 ]. These data not only underline the clinical relevance of these cells, but also suggest that probing CFTR expression/activity and associated biomarkers such as metalloproteinase 9 (MMP9) in peripheral blood leukocytes might have a possible clinical application such as the monitoring the efficacy of CFTR modulators [ 45 , 46 , 47 , 48 ].…”
Section: Leukocytes and Cystic Fibrosismentioning
confidence: 99%
“…Considering that the clinical responses to CFTR modulators vary by, and even within, genotypes [ 68 , 69 , 70 , 71 ], and also that studies examining individuals before and after initiation of CFTR modulators have shown that these molecules do not reverse all disease manifestations [ 66 , 67 , 72 ], it is of great relevance to find biomarkers for monitoring therapies, particularly those predictive of an individual patient’s response. In the last decade, many studies have indicated that leukocytes, being easily and quickly isolated from patients, can be non-epithelial cellular models useful to monitor the responses of CF patients to the treatment during clinical trials and also as potential predicting biomarkers of the efficacy of therapies [ 45 , 47 , 73 ]. To this end, several approaches have been adopted.…”
Section: Toward Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation